Diseño de un Centro de Interpretación del Patrimonio en el Campus Salache. - Criollo Bautista, Darwin Paúl (2020)
Due to the lack of knowledge and the absence of culture, the citizenship has caused negative impacts to the natural and cultural environment that are located in a specific place, therefore, this research had as the main goal to contribute to the conservation of the heritage encouraging the care and the importance through the design of a Heritage Interpretation Centre (HIC) in the Salache Campus. For this, the technical feasibility of the area was determined, through a diagnosis analyzing the current state, the field methodology was applied through direct observation and documentary analysis, a record of scale and parameters was applied and adapted, valued at the scale of Deficient (1-11), Regular (12-22), Good (23-33), Very Good (34-44), Excellent (45-55). The diagnosis concluded that the ranch house has the minimum conditions for the operation of the Interpretation Centre with the functionality of Very Good (34-40) with a total of 40. Furthermore, the thematic areas of the HIC were defined through an analysis of the visitors' demand and the minimum physical space required, according to the visitors' demand who have entered the Salache Campus in the years of 2010-2019, the thematic areas were designed according to the target audience which in this case is the middle childhood from 7 to 11 years old. The most important topics found in the MINEDUC books as a reference to the Natural and social science helped to the definition of the thematic areas, being selected: the Natural resources, biodiversity, importance of conservation, and the interaction of the biotic and abiotic beings, once analyzed, these defined four thematic areas: Cotopaxi audio-visual tours, biodiversity, Salache's resources, and environmental guardians. Finally, the interpretive media were designed with technical criteria that look to contribute to the environmental consciousness of the visitors through records. For the thematic area: Cotopaxi auto visual tour was divided into 8 rooms with a total of 14 interpretative media. For the thematic area: Biodiversity, 1 room with 7 interpretative media. For the thematic area: Salache’s resources, 1 room with 6 interpretative media. For the thematic area: Environmental guardians, 1 room with 4 interpretative media, giving a total of 32 interpretative media with topics related to natural and cultural resources of the Cotopaxi province. This indicates that the study area located in the Salache Campus accomplish with the necessary parameters for the creation of a HIC because it has the dimensions and enough space to make the design. Also, it is recommended to generate other touristic alternatives of awareness, care, and protection of the natural and cultural resources inside the campus, to promote heritage preservation.